CRITICAL ANALYSIS OF RADIOLOGICAL EVALUATION OF GENITOURINARY DISORDERS. - SULTAN KHALID MOHAMMED ALSUBHI, MESHAL ALI TURYES ALOUFI, ABDULAZIZ KHALAF ZAYED ALHARTHI, HUSSAIN AHMED TURAIKHM ALZHRANI, MOHAMMED ATIAH AWAD AL-THAQAFI, MUTLAQ RAJA ALBAQAMI, NAHEDH ZABEN ALHARBI, SAIED SALEH ALAMRI (Chelonian Research Foundation, 2022)
The radiological examination is vital in diagnosing and managing genitourinary problems. The critical evaluation below unfolds the present circumstances of radio-diagnostic methods used to detect diseases of the genitourinary system, including imaging modalities, diagnostic accuracy, and challenges. The origination of scientific literature review and evidence-based analysis in this study results in the identification of crucial findings, the sharing of knowledge about the positives and negatives, and the recommendation of the use of radiological imaging in genital-urinary diseases. Keywords: Radiology, Genitourinary diseases, Imaging modalities, Diagnostic Accuracy, and the Challenges.